High levels of p19/nm23 protein in neuroblastoma are associated with advanced stage disease and with N-myc gene amplification. - Hailat, N (1991)
The gene encoding a novel protein designated nm23-H1, which was recently identified as identical to the A subunit of nucleotide diphosphate kinase from human erythrocytes, has been proposed to play a role in tumor metastasis suppression. We report that untreated neuroblastoma tumors contain a cellular polypeptide (Mr = 19,000) designated p19, identified in two-dimensional electrophoretic gels, which occurs at significantly higher levels (P = 0.0001) in primary tumors containing amplified N-myc gene. The partial amino acid sequence obtained for p19 is identical to the sequence of the human nm23-H1 protein. An antibody to the A subunit of erythrocyte nucleotide diphosphate kinase reacted exclusively with p19. In this study, significantly higher levels of p19/nm23 occurred in primary neuroblastoma tumors from patients with advanced stages (III and IV) relative to tumors from patients with limited stages (I and II) of the disease. Even among patients with a single copy of the N-myc gene, tumors from patients with stages III and IV had statistically significantly higher levels of p19/nm23 than tumors from patients with stages I and II. Our findings indicate that, in contrast to a proposed role for nm23-H1 as a tumor metastasis suppressor, increased p19/nm23 protein in neuroblastoma is correlated with features of the disease that are associated with aggressive tumors. Therefore, nm23-H1 may have distinct if not opposite roles in different tumors.